Maintenance Treatment for Patients With Mantle Cell Lymphoma: A Systematic Review and Meta-analysis of Randomized Trials. Issue 4 (August 2018) - Vidal, Liat; Gafter-Gvili, Anat; Dreyling, Martin; Ghielmini, Michele; Witzens-Harig, Mathias; Shpilberg, Ofer; Unterhalt, Michael; Rummel, Mathias; Gurion, Ronit
Abstract : Abstract: Current treatment of patient with mantle cell lymphoma (MCL) is insufficient and does not result in cure. To assess the efficacy and safety of maintenance therapy for patients with MCL, we performed a systematic review and meta-analysis of randomized controlled trials. Six trials randomizing 858 patients were included in the meta-analysis. In 5 trials, maintenance therapy consisted of rituximab. The pooled hazard ratio (HR) of death with rituximab maintenance compared to observation was 0.79, 95% CI 0.58 to 1.06 (4 trials, 737 patients). Progression free survival was longer with rituximab maintenance in each of the trials and in the pooled analysis (HR 0.58, 95% CI 0.45–0.73). The risk of neutropenia was higher with maintenance compared to observation risk ratio (RR) 1.31, 95% CI 1.03 to 1.66. None of the trials reported on quality of life outcomes. The grade 3 to 4 infection rate was 7% in each of the treatment groups. The risk of grade 3 to 4 infection was not affected by allocation to maintenance. Rituximab maintenance is recommended after R-CHOP or R-cytarabine-containing induction in the frontline setting for transplant eligible and ineligible patients, and after R-CHOP in the relapse setting. It is unclear if maintenance is of benefit after different induction chemotherapy such as bendamustine or fludarabine. It is too early to conclude on other type of maintenance for MCL patients. Abstract : Supplemental Digital Content is available in the text